THE CONCEPT OF PHRASEOLOGICAL ETYMOLOGY AND ITS RESEARCH CRITERIA - Achilov Muzaffar Norkuliyevich (Web of Journals Publishing, 2026)
In this scientific article, we will first examine the essence of the concept of phraseological etymology and the origin, historical roots, and sources of formation of phraseological units of the language, i.e. idioms, phrases, and stable word combinations, from a linguistic perspective.
Keywords: Linguistics, phraseological etymology, lexical meaning.